Micro-nutrient related malnutrition and obesity in a university undergraduate population and implications for non-communicable diseases - Foluke A Olatona; Sunday A Aderibigbe; Eyitope O Amu; Oluseye O Onabanjo; Kelechi E Nnoaham (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background Micronutrient deficiency and obesity are increasing globally. This study determined the prevalence of micronutrient-related malnutrition, patterns of obesity using different methods of assessment, and the predictors of obesity among the university undergraduate population in Lagos State, Nigeria. # Methods A multistage sampling technique was adopted to select 506 students from the three universities in Lagos State. A pre-tested, semi-structured interviewer-administered questionnaire was used to obtain data on socio-demographic and economic characteristics. Nutrient intakes were estimated from 24-hour dietary recalls, obesity was assessed through anthropometric measurements and Bio-electrical Impedance Analysis, following standard procedures. Associations between variables were tested using Chi-square, Fischer's exact tests, and logistic regression analyses. Twenty-four-hour diet recall was analyzed using the Total Diet Assessment soft-ware. Anthropometric indices were compared with World Health Organization (WHO) standards and classified. # Results Mean daily intake of almost all micronutrients was low except sodium which was in excess compared to the recommended dietary allowances. The prevalence of underweight was 6.6%, overweight (16.4%), and obesity (3.2%) based on body mass index (BMI). Abdominal obesity was higher than general obesity. Obesity assessed using the percentage body fat had the highest yield of 54.4% in males and 37.1% in females. # Conclusions Micronutrient-related malnutrition and central obesity were higher than reported in previous studies. Male gender, inconsistent income, and increased amount of folate were significant predictors of obesity. The students will benefit from nutrition education that emphasize the consumption of micronutrient dense foods and different methods of weight management.